Disney's Atlantis Milo's return - Hart, Thomas; Stones, Tad.; Shelton, Toby.; Cook, Victor A.; Walt Disney Television Animation; Viva Video, Inc.; Walt Disney Home Entertainment (Firm).; Buena Vista Home Entertainment (Firm). ([United States] Burbank, Calif. Walt Disney Home Entertainment distributed in the Philippines by Viva Video, 2003)
Milo, Kida and their team gear up for more action when trouble surfaces above water, threatening the famous and mysterious underwater kingdom of Atlantis. They discover that mystifying powers are at work.
Animators, Roland Angelo ... [et al.] ; editor, John Royer ; original music, Don Harper ; character designers, Dana Landsberg, Kenny Thompkins, Mark Cote, Benjamin Balistreri.
Voices: James Taylor, Cree Summer, John Mahoney, Jacqueline Obradors, Don Novello, Corey Burton.
MPAA rating: G.
VCD, Dolby digital, 5.1 surround sound, DTS 5.1 digital surround sound.
Keywords: Atlantis (Legendary place) -- Juvenile drama; Feature films; Animated films; Children's films